2019
DOI: 10.1111/cid.12793
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss around oral and orthopedic implants: An immunologically based condition

Abstract: Background: Marginal bone resorption has by some been identified as a "disease" whereas in reality it generally represents a condition.Purpose: The present article is a comparison between oral and orthopedic implants, as previously preferred comparisons between oral implants and teeth seem meaningless. Materials and Methods:The article is a narrative review on reasons for marginal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 88 publications
(182 reference statements)
2
55
0
Order By: Relevance
“…Osseointegration has been suggested to represent a foreign body reaction to biomaterials and its long-term clinical function depending on a foreign body equilibrium that, if disturbed, may lead to impaired clinical function of the implant [15]. Recently, dental implants have been suggested having more in common to orthopaedic implants in terms of foreign body reaction and failure pattern than to teeth [16]. Given these fundamental differences between the periodontal and peri-implant tissues, can periodontal indices be used as reliable diagnostic tools for peri-implant tissues?…”
Section: Introductionmentioning
confidence: 99%
“…Osseointegration has been suggested to represent a foreign body reaction to biomaterials and its long-term clinical function depending on a foreign body equilibrium that, if disturbed, may lead to impaired clinical function of the implant [15]. Recently, dental implants have been suggested having more in common to orthopaedic implants in terms of foreign body reaction and failure pattern than to teeth [16]. Given these fundamental differences between the periodontal and peri-implant tissues, can periodontal indices be used as reliable diagnostic tools for peri-implant tissues?…”
Section: Introductionmentioning
confidence: 99%
“…Other foreign bodies routinely seen adjacent to implants such as titanium particles [24,25,26] or the accidental presence of cement in the bone-to-implant interface that, according to some investigators, may be found in 59% of cemented implants [27], may combine to cause peri-implantitis [28].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, oral implants evoke a mild immunoreaction. And implants survive in the body in a delicate positive immune balance based on the individual host immune system [26,27]. Titanium ion may be a possible factor to disrupt this balance.…”
Section: Discussionmentioning
confidence: 99%